2019
DOI: 10.1155/2019/3821082
|View full text |Cite
|
Sign up to set email alerts
|

Study of PEM Fuel Cell End Plate Design by Structural Analysis Based on Contact Pressure

Abstract: A fuel cell stack is configured to power any load ranging from watts to megawatt by varying cells connected in series. During stack assembly, major emphasis must be placed on application of adequate external pressure for reducing the ohmic losses, the purpose of which is to achieve proper contact between the cell components and minimize the contact resistance. Present work aims to study the influence of geometry of the cell, bolt configuration, gasket thickness mismatch, and material properties of different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…[ 515 ] A non‐uniform pressure distribution can result in a lack of electrical contact toward the MEA center, which can have a significant effect on the local performance. [ 516,517 ] This can be solved by using thicker endplates, [ 517,518 ] bladder cells, [ 519 ] or increasing the clamping pressure. [ 520 ]…”
Section: Catalyst Layer Preparation Methodsmentioning
confidence: 99%
“…[ 515 ] A non‐uniform pressure distribution can result in a lack of electrical contact toward the MEA center, which can have a significant effect on the local performance. [ 516,517 ] This can be solved by using thicker endplates, [ 517,518 ] bladder cells, [ 519 ] or increasing the clamping pressure. [ 520 ]…”
Section: Catalyst Layer Preparation Methodsmentioning
confidence: 99%
“…Pressure is approximated depending on the density of red spots. The second tool for evaluating the pressure distribution is the use of piezoelectric sensors, as in the work of Dey et al [36].…”
Section: Comparison With Literaturementioning
confidence: 99%
“…Dey, T. et al [10] studied the effect of End Plates shape and the number of bolt on the distribution of contact pressure. Several geometries were studied numerically (extruded hexagonal, extruded triangles, plain flat) and have shown that the extruded hexagonal geometry presents better distribution of contact pressure all over the contact surface, with a contact resistance per unit surface that varies from R = 0 to 30Ω.…”
Section: Mechanical Parametersmentioning
confidence: 99%